Mansai in the Marriage Tradition of the Banggai Ethnic in Central Sulawesi, Indonesia: A Living Sunnah Perspective - Puyu, Darsul S.; Umar, Subehan Khalik; Hanis, Hasdin; Arifin, Bustanul; Abili, Muhammad (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
The Mansai tradition is the custom of collecting material assistance before the wedding to lighten the burden on the prospective groom. This procession becomes a problem whether it is in harmony with the Prophet's orders. This study is qualitative research using the approach of living traditions and anthropology of Islamic law. Living sunnah is used to analyze the concept of hadith that lives in the Banggai community, while the anthropology of Islamic law analyzes the practice of mansai which is a tradition in marriage. Data was collected by gathering information through in-depth interviews and literature studies. The field findings were then analyzed using the perspective of living sunnah and integrated with the customs of the people of the Banggai Tribe, Central Sulawesi. The selected hadiths are those that have been validated for the quality of their sanad and matan. This study found that the mansai tradition means that the prospective groom invites his family and community to bear the funds or assets as wedding expenses which will be handed over to the woman (mangantokon sai). Mansai as a custom has become a habit in accordance with Islamic law and has become a living sunnah. The main message in the Mansai tradition is to help each other and ease the burden on Muslim brothers and sisters in the process of marriage (banikah) in the Banggai Tribe community. Anthropologically, mansai as a tradition that has been accepted by the Banggai people for a long time, functions as a unifying medium, maintains the practice of deliberation and overcomes social problems.